An insertion heuristic for the capacitated vehicle routing problem with loading constraints and mixed linehauls and backhauls - Pinto, Telmo (2015)
In this paper, a capacitated vehicle routing problem with mixed linehauls and backhauls is presented. The addressed problem belongs to the subclass of pickup and delivery problems. Loading and sequencing constraints are also considered. These constraints arise in many realworld situations, and can improve efficiency since backhaul customers do not need to be delayed in a route when it is possible to load their items without rearrengements. The suggested approach is based on an insertion heuristic presented in the literature but extended to tackle the explicit consideration of loading constraints. Different strategies are presented and tested. An exhaustive computational study is performed on instances adapted from benchmark instances for integrated routing and loading problems.